Rural-urban migration as a risk coping strategy: The role of income differentials - Sylvie Démurger; Siwar Khelifa; Béatrice Rey (University of Neuchâtel, Institute of Economic Research (IRENE), 2023)
This paper investigates how rural-urban income differentials interact with the risk coping motive to shape households' migration behavior. Using a model of migration behavior under agricultural income risk, our theoretical results suggest that while income differentials remain crucial in determining the migration decision, they are additionally determined by the agricultural income risk the household is facing. Empirical findings on Chinese farm households indicate that the incidence of migration as a risk coping mechanism is lower for households with a negative expected urban-to-rural income difference. Moreover, we find that, when these households care about the human capital of their children, their marginal utility of income increases as the educational performance of their children deteriorates, implying that, when migration is used as a risk coping strategy, households with lower educational performance of children may be more likely to send a parent for migration. This result also suggests that the best specification of the utility function to consider for these households is the non-separability between the household's earnings and their children's human capital.
Keywords: D81; J13; J31; J61; O15; O53; R23; 330; labor migration; aggregate risk; income differential; China